Bibliometric analysis of the pirfenidone and nintedanib in interstitial lung diseases - Jia Liu; Faping Wang; Yiwen Hong; Fengming Luo (Heliyon, 2024)
Background: At the beginning of 21st century, reclassification of fibrosing interstitial lung diseases (ILD) scored academic concerning, and then propelled development. Decade before, pifenidone and nintedanib were approved for idiopathic pulmonary fibrosis, but no more drugs are yet available. To evaluate the development traits of pirfenidone and nintedanib in fibrosing ILD, including the influential country, institution, authors, keywords, and the major problems or the priorities of the field emerge and evolve, bibliometric analysis was used to summarize and draw scientific knowledge maps. Methods: We confined the words to “pirfenidone”, “nintedanib”, “pulmonary fibrosis”, and “lung disease, interstitial”. Publications were retrieved from the Web of Science Core Collection on February 24, 2024 with the search strategies. Citespace and VOSviewer were adopted for bibliometric analysis. Results: For the knowledge map of pirfenidone, a total of 4359 authors from 279 institutions in 58 countries/regions contributed to 538 studies. The United States and Italy are way ahead. Genentech Inc and the University of Turin are the institutions with the strongest influence. AM J RESP CRIT CARE is the maximized influential periodical. Raghu G was the most frequently co-cited scholar. keywords cluster demonstrated that vital capacity, safety, outcome, effectiveness, acute exacerbation, pathway, cell, collagen were the hotspots. The burst timeline of hotspots and references revealed academic transitions of pirfenidone-related studies. About the knowledge map of nintedanib, 3297 authors from 238 institutions in 47 countries/regions published 374 studies. Japan, the United States, and Italy are the most productive countries. Boehringer Ingelheim is the overriding productive institution. New ENGL J MED have important roles in reporting milestones of nintedanib. Richeldi L carried numerous capital publications to support the anti-fibrotic effect of nintedanib. From the network of co-occurrence keywords, idiopathic pulmonary fibrosis, efficacy, and safety were the hotspots. Nintedanib for systemic sclerosis-related ILD and progressive pulmonary fibrosis is the hotspot with sharp evolution recently. Conclusions: We summarized and showed developmental alterations of pirfenidone and nintedanib in fibrosing ILD through bibliographic index-based analysis. Our findings showed just dozen years sharp development period of pirfenidone and nintedanib in ILD, and identifies potential partners for interested researchers. The burst of hotspots demonstrated the evolvement of research priorities and major problems, and we observed the transition of keywords from experimental terms like mouse, bleomycin, cell, pathway, collagen, gene expression, to clinical terms including efficacy, safety, survival, acute exacerbation, and progressive pulmonary fibrosis. In the future, exploration about disparity models of drug administration, differences between early and later initiate anti-fibrotic therapy, both short-term and long-term efficacy of pirfenidone and nintedanib in fibrosing ILD, specifically in connective disease associate ILD would be emphatically concerned by pulmonologists.